Recommendations for monitoring avian populations with point counts: a case study in southeastern Brazil - Cavarzere, Vagner; Moraes, Gabriel Parmezani; Roper, James Joseph; Silveira, Luís Fábio; Donatelli, Reginaldo José (Papéis Avulsos de Zoologia, 2013)
In the northern hemisphere, bird counts have been fundamental in gathering data to understand population trends. Due to the seasonality of the northern hemisphere, counts take place during two clearly defined moments in time: the breeding season (resident birds) and winter (after migration). Depending on location, Neotropical birds may breed at any time of year, may or may not migrate, and those patterns are not necessarily synchronous among species. Also in contrast to the northern hemisphere, population trends and the impact of rapid urbanization and deforestation are unknown and unmonitored. Throughout one year, we used point counts to better understand temporal patterns of bird species richness and relative abundance in the state of São Paulo, southeastern Brazil, to examine how to implement similar bird counts in tropical America. We counted birds twice each day on 10 point transects (20 points day‑1), separated by 200 m, with a 100 m limited detection radius in a semideciduous tropical forest. Both species richness and bird abundance were greater in the morning, but accumulation curves suggest that longer-duration afternoon counts would reach the same total species as in morning counts. Species richness and bird abundance did not vary seasonally and unique species were counted every month; relatively few species (20%) were present in all months. Most (84%) known forest species in the area were encountered. We suggest that point counts can work here as they do in the northern hemisphere. We recommend that transects include at least 20 points and that the simplest timing of bird counts would also be seasonal, using timing of migration of austral migrants (and six months later) to coordinate counts. We propose that bird counts in Brazil, and elsewhere in Latin America, would provide data to help understand population trends, but would require greater effort than in temperate latitudes due to greater species richness and different dynamics of reproduction and migration. With collaboration among ornithologists and coordinated bird surveys, we may develop a technique for the tropics that would yield information for population trends and conservation of birds, similar to counts in temperate latitudes.